Mechanical and oxygen barrier properties of sodium caseinate edible film - Yap, Yuh Ming; Abdul Rahman, Russly; Chin, Nyuk Ling (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Petroleum based packaging material wastes have always been associated with negative environment impacts. Hence, the demand for renewable yet environmental friendly packaging materials have been in the rise. Various natural resources such as proteins, polysaccharides, and lipids have been used in developing edible films and coatings. Particularly, caseinate with natural open and flexible chemical structure has excellent film forming ability. The main purpose of the study was to develop edible films from various levels of sodium caseinate, sorbitol and palm olein (cooking oil). The physical properties of the edible films were evaluated and compared with the commercially produced cling film. Edible films were prepared using casting method and dried in an oven for 24 hours. Dried films were conditioned in the storage with relative humidity 55±3% at 23±2ºC for at least 48 hours prior to evaluation. Overall, edible films developed for the study were found to have better oxygen barrier property than the cling film. It was also found that, cling film had higher tensile strength and better elongation properties than the developed edible films. For Young's modulus, edible films with sodium caseinate: sorbitol at 1:0.25 had higher Young's modulus value than cling film. The good oxygen barrier property exhibited by sodium caseinate edible films may prolong the shelf life of food.